2017
DOI: 10.1192/bjp.bp.116.197640
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversities and post-traumatic stress disorder: evidence for stress sensitisation in the World Mental Health Surveys

Abstract: Background Although childhood adversities are known to predict increased risk of post-traumatic stress disorder (PTSD) after traumatic experiences, it is unclear whether this association varies by childhood adversity or traumatic experience types or by age. Aims To examine variation in associations of childhood adversities with PTSD according to childhood adversity types, traumatic experience types and life-course stage. Method Epidemiological data were analysed from the World Mental Health Surveys (n = 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 58 publications
(73 reference statements)
3
108
0
2
Order By: Relevance
“…Indeed, it is reported that more than half of patients with PTSD have comorbid depressive disorders . Moreover, early‐life adversities, such as childhood maltreatment, are known to increase risk of PTSD in later life . In particular, depression and history of childhood maltreatment have also been associated with increased inflammation; therefore, these conditions can confound the association between PTSD and inflammation.…”
Section: Inflammation and Ptsdmentioning
confidence: 99%
“…Indeed, it is reported that more than half of patients with PTSD have comorbid depressive disorders . Moreover, early‐life adversities, such as childhood maltreatment, are known to increase risk of PTSD in later life . In particular, depression and history of childhood maltreatment have also been associated with increased inflammation; therefore, these conditions can confound the association between PTSD and inflammation.…”
Section: Inflammation and Ptsdmentioning
confidence: 99%
“…As a result, very little research has evaluated the interconnections between child maltreatment and other forms of trauma. In one example of research examining variation in the associations of various childhood adversities with PTSD, McLaughlin and colleagues (2017) analyzed data from a large, nationwide sample collected by World Mental Health Surveys. Results indicated that physical and sexual abuse, neglect, and parent psychopathology all predicted similar odds of developing PTSD, whereas interpersonal loss, parental maladjustment, serious physical illness, and economic adversity did not predict PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral sensitization refers to a process whereby traumaassociated stress (but also repeated use of substances of abuse, mood or anxiety episodes, and suicide attempts) sensitize behavioral, motivational and stress systems, thereby increasing the behavioral and physiological reactivity to subsequent stressors or other sensitizing agents even after a prolonged absence of those agents (15)(16)(17)(18). Consistent with findings in animals, research in humans showed at least three different aspects of behavioral sensitization: induction, the development of behavioral sensitization to a sensitizing agent, including uncontrollable stressors (19), substances of abuse (18,20,21), and, in PTSD, repeated illness episodes (22); expression, exaggerated behavioral or physiological responses to a sensitizing agent even after prolonged absence of that agent (18,21,23); and cross-sensitization, the process by which sensitization to one agent results in sensitization to other agents (e.g., facilitation of behavioral sensitization to psychostimulants after exposure to uncontrollable stress) (24).…”
Section: Functional Mechanismmentioning
confidence: 99%